PENGARUH ACTIVE BIRTH TERHADAP PROSES PERSALINAN KALA I FASE AKTIF - Susanti, Eni; Happinasari, Ossie; Utami, Laela Rizqi; ., Indriyani (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
ABSTRACT: THE EFFECT OF BIRTH ON THE ACTIVE PHASE OF THE FIRST STAGE OF LABOR IS THE ACTIVE. The delivery is ending with a series expenditure term infants born 37-42 weeks spontaneously, without the complications of both the mother and the fetus, followed by the expulsion of the placenta and fetal membranes of the mother's body. Active Birth is the process in which the birth mother is recommended as an active participant, allowing the mother to find a position that makes it comfortable and reduce pain. (Balaskas,2004). This reseach want to analyze the influence of the Active Birth to the active phase of the first stage of labor. The method of research used in this study is a quasi - experiment (quasi-experimental ) design with two group pretest - posttest design comparrison . In the observations made in this design as much as 2 times that prior to treatment and after treatment , there were 2 groups compared the results after the 2 groups treated . The technique of sampling is accidental sampling ie sampling by chance, in this case maternal encountered during the normal maternal emphasis of 30 people with 15 people doing technical details of active birth and 15 did not perform active birth. The Statistical test results of independent t pain intensity in the non - active and active birth birth prior to treatment was obtained M = 8.33 and SD = 0.983 difference in the non - active birth, whereas in the active group obtained birth M = 8, 67 and SD = 0.724 . Based on 28 degrees of freedom with a significance level of 0.05 is obtained t -1.357 (p = 0.186). It can be concluded that there is no significant difference between the mean pain intensity in the non - active and active birth birth prior to treatment. Results of independent t test statistic pain intensity in the active group of non - active birth and birth after treatment obtained M = 8.13 and SD = 0.516 at birth while the active group in the non - active birth obtained M = 5.47 and SD = 0.915 . Of table 5 by 28 degrees of freedom with significance level of 0.05 t 9.826 obtained (p = 0.000). So we can conclude that H0 is rejected, which means that there are significant differences between the mean pain intensity in the group of active and non - active birth after birth do massage. Conclusion: No effect of birth on the active phase of the first stage of labor is the active.Keywords: Active Birth, Labor, The Aktif of First Phase